(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
A method for fabricating longitudinally operating cadmium selenide photosensitive films and transparent conductive contacts on SnO2 and CdO is presented. It is shown that photosensitive films with stable and reproducible electrophysical characteristics are obtained using annealing temperatures in air in the presence of CdCl2 of -470°C; and CuCl2 of -300°C.